Generic Cost-Effectiveness Models: A Proof of Concept of a Tool for Informed Decision-Making for Public Health Precision Medicine - Snyder, Susan R.; Hao, Jing; Cavallari, Larisa H.; Geng, Zhi; Elsey, Amanda; Johnson, Julie A.; Mohamed, Zahurin; Chaiyakunapruk, Nathorn; Chong, Huey Yi; Dahlui, Maznah; Shabaruddin, Fatiha Hana; Patrinos, George P.; et al. (Karger Publishers, 2019)
Background/Aims: Economic evaluation is integral to informed public health decision-making in the rapidly growing field of precision and personalized medicine (PM); however, this research requires specialized expertise and significant resources. Generic models are a novel innovation to efficiently address a critical PM evidence shortage and implementation barrier by enabling use of population-specific input values. This is a generic PM economic evaluation model proof-of-concept study for a pharmacogenomic use case. Methods: An 8-step generic economic model development process was applied to the use case of human leukocyte antigen (HLA)-B∗15:02genotyping for prediction of carbamazepine-induced cutaneous reactions, with a user-friendly decision-making tool relying on user-provided input values. This generic model was transparently documented and validated, including cross-validation comparing cost-effectiveness results with 3 country-specific models. Results: A generic pharmacogenomic use case cost-effectiveness model with decision-making tool was successfully developed and cross-validated using input values for 6 populations which produced consistent results for HLA-B∗15:02 screening at country-specific cost-effectiveness threshold values. Differences between the generic and country-specific model results were largely due to differences in model structure and assumptions. Conclusion: This proof on concept demonstrates the feasibility of generic models to provide useful PM economic evidence, supporting their use as a pragmatic and timely approach to address a growing need. © 2019 S. Karger AG, Basel. All rights reserved.